Avian Influenza Virus: Comparative Evolution as the Key for Predicting Host Tropism Expansion - Matteo Mellace; Carlotta Ceniti; Marielda Cataldi; Luca Borrelli; Bruno Tilocca (Pathogens, 2025)
The avian influenza virus poses an emerging public health risk due to its ability to cross the species barrier and infect a broad spectrum of hosts, including humans. The aim of this study was to investigate the molecular mechanisms and evolutionary dynamics underlying the spillover, using a bioinformatics approach to viral sequences. Eight viral proteins involved in the process of adaptation to new hosts were selected, and 156 amino acid mutations potentially associated with interspecies transmission were analyzed. The sequences, obtained from the NCBI Virus database, were aligned with the BLASTP1.4.0 tool and compared through phylogenetic analysis. The results show significant evolutionary proximity between human and animal viral strains, and the identification of shared mutations suggests the presence of conserved mechanisms in spillover. The identification of hosts that share mutations with human strains highlights the potential role of these animals as reservoirs or vectors. This study contributes to the understanding of viral adaptation and provides a starting point for targeted preventive strategies, including molecular surveillance and the development of containment and prevention measures.